Sosialisasi Cara Pembuatan ID Card Berbasis Barcode di Desa Baujeng Kabupaten Pasuruan - Muchammad Firman; Muslim Alamsyah; Cindy Amelia Lestari (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2023)
This activity is a community service program which aims to provide training to the community in Baujeng Village, Beji District, Pasuruan Regency, East Java. This program includes training in making Barcode-based ID Cards with implementation methods that include initial planning, collection of materials and resources, program implementation, evaluation, follow-up, documentation, reporting and dissemination of results. The partner of this program is Pondok Minhajuttulab, an Islamic boarding school which acts as a place for socialization. Problems to be overcome include a lack of understanding and exposure to modern technological developments in Baujeng Village. This program also includes evaluation through questionnaires and recording the problems faced by participants during the activity. The aim of this program is to increase community participation in digital transformation and serve community needs efficiently using computer technology